CHARACTERISTICS OF INTERNET USE AS A MEANS OF PERCEIVED STRESS REDUCTION IN HEALTH CARE STUDENTS - Hinić, Darko; Jović, Jelena; Ignjatović Ristić, Dragana (Specijalna edukacija i rehabilitacija, 2016)
Previous studies suggest that people use media for instrumental needs, entertainment/leisure or for social gratification. The aim of this study is to identify specific characteristics of Internet use in health care students who use the Internet as a means of perceived stress reduction. The sample included 231 students (m=34%; f=66%), aged (M=22.44; SD=2.09), who were subsequently categorised into two groups according to whether they consciously use the Internet to alleviate the consequences of stressful experiences. The individuals reporting the Internet as a means of perceived stress reduction spend considerably more time online than other Internet users. They also use contents related to entertainment, culture and sex more frequently, as well as social applications and networks. In comparison to others, these participants meet new people and potential partners more often via the Internet, spend more time on their friends' profiles, while using different entertainment applications, most commonly games. The Internet may play a significant role in reducing negative reactions to stressful events; therefore, we may regard cyberspace as a fertile ground for educational, preventive and counselling services. The main limitation to the current study is the sample (only health care students). Future studies should include assessment of perceived stress levels and their relation to study variables.
Keywords: Internet use; health care students; mood management theory; stress; Uses and gratification theory